Bacterial leakage evaluation of root canals filled with different endodontic sealers - Pinheiro, Claudia Ramos [UNESP]; Guinesi, Adriana Simionatto [UNESP]; de Camargo, Ericson Janolio; Pizzolitto, Antonio Carlos [UNESP]; Bonetti Filho, Idomeo [UNESP] (Mosby-elsevier, 2009)
Objective. The objective of this study was to evaluate the sealing ability of AH Plus, Epiphany, Acroseal, Endofill, and Polifil after active lateral condensation technique, by using a bacterial test, during 64 days.Study design. One hundred bovine incisors were cleaned and shaped; then they were filled with the endodontic sealers and adapted into a microcentrifuge tube. The setup root/microcentrifuge tube was added to glass flasks containing Brain Heart Infusion broth. A culture of Enterococcus faecalis was inserted into the upper chamber of each assembly. Daily leakage was evaluated through the broth turbidity.Results. The results were submitted to statistical analysis (Kaplan-Meier method, Kruskal-Wallis and Dunn tests).Conclusions. AH Plus and Endofill had the worst sealing ability when compared with Polifil, which showed the least leakage. Acroseal and Epiphany showed a tendency toward having an intermediate behavior; however, there was no significant difference among Acroseal, Epiphany, and the other sealers. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2009; 108: e56-e60)